Simultaneously measured inter-arm blood pressure difference is not associated with pulse wave velocity in a clinical dataset of at-risk hypertensive patients - Nolde, Janis M.; Lugo-Gavidia, Leslie Marisol; Kannenkeril, Dennis; Chan, Justine; Robinson, Sandi; Jose, Ancy; Joyson, Anu; Schlaich, Luca; Carnagarin, Revathy; Azzam, Omar; Kiuchi, Márcio Galindo; Schlaich, Markus P. (Journal of Human Hypertension, 2021)
Recent analysis of systolic inter-arm differences in blood pressure from the INTERPRESS-IPD Collaboration suggest an association with increased all-cause mortality, cardiovascular mortality and cardiovascular events. Previous studies have demonstrated associations with other risk parameters. We aimed to reproduce these associations in a cohort of 199 treated, at-risk hypertensive patients with pulse wave velocity (PWV) as a surrogate marker of cardiovascular (CV) damage. Simultaneously measured inter-arm blood pressure (BP) differences, 24 hour ambulatory BP and PWV were measured in 199 treated patients from a tertiary hospital hypertension outpatient clinic. Associations between systolic inter-arm BP difference and PWV were analyzed with uni- and multi-variate regression models. Out of 199 participants, 90 showed an inter-arm BP difference of more than 5 mmHg. The inter-arm difference was not associated with PWV. Furthermore, neither observed single BP measurements nor 24 hour ambulatory BP was associated with inter-arm BP differences. In our clinical patient cohort we failed to observe an association between inter-arm BP differences and PWV. Mode of assessment, study design and the sample characteristics of this treated, hypertensive cohort may have contributed to the negative findings. The limited sample size of the study poses a challenge to the detection of smaller effects in our study.
CRIS-Team Scopus Importer:2021-08-13